(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2011)
In this paper, I will be exploring the phenomenon of ’barebacking’ or UAI, the practice of unprotected anal intercourse. I will be hoping to clarify how this currently expanding phenomenon, and the reality of the complexity of issues that underpin the practice itself, can be viewed from an existential and phenomenological perspective. These issues involve passion and desire, need and fulfillment, self-discovery and self harm, values and relationships, isolation and community, power and politics, empowerment and death. We must also take into consideration that we are being confronted by a sexual version of Russian Roulette. I propose to use the work of Existential Philosophy and modern writers on this subject, and also my own experience with clients who are facing the dilemma of either safe-sex or bareback practice.